2021
DOI: 10.9734/ajess/2021/v14i130348
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Vitamin D Insufficiency among Adults with Epilepsy at University Hospital in Jeddah, Saudi Arabia: A Cross Sectional Study

Abstract: Background: Vitamin D is essential for bone physical condition, and vitamin D insufficiency may add to further autoimmune diseases, infections or even cancer. Enzyme-inducing antiepileptic drugs have been predominantly linked with osteoporosis hazard proved their impacts on vitamin D. The study aim was to determine the prevalence of vitamin D insufficiency and deficiency and the covariates associated with it among the adult epileptic patients attending King Fahd neurology outpatient clinics. Subjects and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Our cohort’s vitamin D deficiency status is relatively higher than what has been reported in other studies [ 12 , 23 , 24 , 25 ]. The prevalence of vitamin D deficiency among adults with epilepsy was 67.3% in a previous study [ 26 ]. Choong Yi Fong et al found vitamin D deficiency in 22.5% of children with epilepsy and 19.7% had vitamin D insufficiency [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our cohort’s vitamin D deficiency status is relatively higher than what has been reported in other studies [ 12 , 23 , 24 , 25 ]. The prevalence of vitamin D deficiency among adults with epilepsy was 67.3% in a previous study [ 26 ]. Choong Yi Fong et al found vitamin D deficiency in 22.5% of children with epilepsy and 19.7% had vitamin D insufficiency [ 12 ].…”
Section: Discussionmentioning
confidence: 99%